Emx2 and Foxg1 inhibit gliogenesis and promote neuronogenesis. - Brancaccio, Marco; Pivetta, Chiara; Granzotto, Marilena; Filippis, Carol; Mallamaci, Antonello (Stem Cells, 2010)
Neural stem cells (NSCs) give rise to all cell types forming the cortex: neurons, astrocytes, and oligodendrocytes. The transition from the former to the latter ones takes place via lineage-restricted progenitors in a highly regulated way. This process is mastered by large sets of genes, among which some implicated in central nervous system pattern formation. The aim of this study was to disentangle the kinetic and histogenetic roles exerted by two of these genes, Emx2 and Foxg1, in cortico-cerebral precursors. For this purpose, we set up a new integrated in vitro assay design. Embryonic cortical progenitors were transduced with lentiviral vectors driving overexpression of Emx2 and Foxg1 in NSCs and neuronal progenitors. Cells belonging to different neuronogenic and gliogenic compartments were labeled by spectrally distinguishable fluoroproteins driven by cell type-specific promoters and by cell type-specific antibodies and were scored via multiplex cytofluorometry and immunocytofluorescence. A detailed picture of Emx2 and Foxg1 activities in cortico-cerebral histogenesis resulted from this study. Unexpectedly, we found that both genes inhibit gliogenesis and promote neuronogenesis, through distinct mechanisms, and Foxg1 also dramatically stimulates neurite outgrowth. Remarkably, such activities, alone or combined, may be exploited to ameliorate the neuronal output obtainable from neural cultures, for purposes of cell-based brain repair.
Keywords: Animals; Cell Differentiation; Cell Enlargement; Cells, Cultured; Female; Forkhead Transcription Factors; Homeodomain Proteins; Mice; Nerve Tissue Proteins; Neurogenesis; Neuroglia; Neurons; Stem Cells; Transcription Factors